Rancang Bangun Pengaman Panel Distribusi Tenaga Listrik Di Lippo Plaza Sidoarjo Dari Kebakaran Berbasis Arduino Nano - Achmad Solih; Jamaaluddin Jamaaluddin (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2017)
Panel system power distribution at Lippo Plaza Mall Sidoarjo consists of several parts, namely from Cubicle 20 KV, 20 KV step-down transformer for 380 V, then the supply to LVMDP (Low Voltage Main Distribution Panel) The new panel to the user. Before delivery to users to note that the power factor is corrected using a capacitor bank. Less good a power factor is turned into inductive load on the capacitor bank so that temperatures high because of high load resulting capacitor bank erupt. To overcome in this study proposes a safety panel automation power distribution control system using a microcontroller. Control system microcontrollers for safety panel power distribution consists of: Microcontroller (Arduino Nano), Light sensor (LDR), temperature sensor (LM35DZ), LCD 16x2 I2C, Actuators (fan, buzzer, relay switch breaker network three phase), switch ( relay 5 VDC), ADC as Input data. The working principle of this microcontroller LM35DZ if the sensor detects a high temperature fan will flash, if the LDR sensor detects sparks then the buzzer will sound as a warning sign of the dangers and disconnected the electricity network. From the design of a safety tool for power distribution panels due to high temperatures or sparks as well as the expected rate of fire outbreaks can be prevented.